Nonenzymatic NADH-Dependent Reduction of Keggin-Type 12-Tungstocobaltate(III) in Aqueous Medium - Prabla Kumari; Alaka Das; Dillip Kumar Baral; A. K. Pattanaik; P. Mohanty (E-Journal of Chemistry)
The kinetics of the electron transfer reaction of NADH with 12-tungstocobaltate(III) has been studied over the range 5.07 ≤ 104 [NADH] ≤ 15.22 mol dm-3, 7.0 ≤ pH ≤ 8.0 and 20 ≤ t ≤ 35 oC in aqueous medium. The electron transfer reaction showed first-order dependence each in [NADH]T and [12-tungstocobaltate(III)]T. The products of the reaction were found to be NAD+ and 12-tungstocobaltate(II). The activation parameters ΔH# (kJ mol-1) and ΔS# (JK-1mol-1) of the electron transfer reactions were found to be 64.4±1.8 and -48.86±6.0. Negative value of ΔS# is an indicative of an ordered transition state for the electron transfer reaction.